2015
DOI: 10.1007/s00217-015-2541-8
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and investigation of inhibitory patterns of flavonoids and phenolic acids on heterocyclic amine formation in chemical model systems by UPLC-MS profiling and chemometrics

Abstract: DMIP formation. The results have demonstrated that the proposed UPLC-MS profiling method may be a useful tool for differentiating and exploring inhibitory patterns of different categories of ingredients from natural origin on HA formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Phenolic compounds (protocatechuic acid, chlorogenic acid, ferulic acid, and p ‐coumaric acid) and flavonoids (naringenin, quercetin, luteolin, and rutin) were also used to inhibit the formation of HAAs, some of which even had 100% inhibition for some certain HAAs (Zeng et al., ; Zeng et al., ; Zhu, Zhang, Wang, Chen, & Zheng, ). Effect of fatty acids (such as conjugated linoleic acid)/oils (such as olive oil) on the formation of HAAs has also been documented in previous works (Lee, Dong, Jung, & Shin, ; Lu et al., ; Oz & Cakmak, ; Oz et al., ).…”
Section: Mitigation Strategies For Haasmentioning
confidence: 99%
“…Phenolic compounds (protocatechuic acid, chlorogenic acid, ferulic acid, and p ‐coumaric acid) and flavonoids (naringenin, quercetin, luteolin, and rutin) were also used to inhibit the formation of HAAs, some of which even had 100% inhibition for some certain HAAs (Zeng et al., ; Zeng et al., ; Zhu, Zhang, Wang, Chen, & Zheng, ). Effect of fatty acids (such as conjugated linoleic acid)/oils (such as olive oil) on the formation of HAAs has also been documented in previous works (Lee, Dong, Jung, & Shin, ; Lu et al., ; Oz & Cakmak, ; Oz et al., ).…”
Section: Mitigation Strategies For Haasmentioning
confidence: 99%
“…On the other hand, the potato peel flour incorporation had a contrary effect to what was expected, increasing the total HCAs content. We expect that the phenolic acids and flavonoids found in potato peel flours (chlorogenic and caffeic acids) could contribute to reducing the HCAs formation in beef patties, as indicated by Zeng et al [ 44 ]. However, it is very important to notice that the exact mechanism of the inhibitory effect of polyphenolic compounds (phenolic acids or flavonoids including anthocyanins) on the total quantity of HCAs remains poorly understood.…”
Section: Resultsmentioning
confidence: 96%
“…The loading plot displaying the distribution of 62 aroma compounds in vinegar samples is shown in Figure 2b. The principal component loading plot can show the contribution of different variables to the principal component, and when the variable in the loading plot is in the same position as the sample in the score plot, it indicated that the variable is the main component of the sample (Cozzolino et al., 2009; Govindaraj et al., 2020; Zeng et al., 2016). As shown in Figure 2a,b, these 40 fermented vinegars were clearly divided into four regions.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the differences between vinegar samples of different raw materials and production technology, chemometric methods such as PCA and PLS-DA were applied and the peak area percentage of volatile components were used as descriptors in these ple (Cozzolino et al, 2009;Govindaraj et al, 2020;Zeng et al, 2016).…”
Section: Pca Analysismentioning
confidence: 99%